An Unusual Case of Dual Left Anterior Descending Artery with Coronary Computed Tomographic Angiographic Correlation - Kyle M. Moulton; Greg Kraushaar; Derek A. Fladeland (Case Reports in Radiology)
Dual left anterior descending artery (LAD) is a rare coronary anomaly that is important to recognize at coronary imaging as it may influence reperfusion strategies. Four types of dual LAD are described by the traditional literature. We present a novel case of dual LAD with coronary computed tomographic angiographic correlation that does not fit into this classification system. Rather, our case supports the recently proposed notion of adding a fifth variant to the traditional dual LAD classification system.